Quantitative Traits of Melodi Gama-3 Melon (Cucumis Melo L.), A New Superior Cultivar, on Rainy Season and Altitude Variation - Rizko Hadi (Pandawa Institute, 2023)
Melodi Gama 3 is a superior melon cultivar candidate which was developed presently. Purposes of this study were to determine quantitative traits of the Melodi Gama 3, as well as to compare it to commercial melon cultivars, based on trial on rainy season and altitude variation. Materials used were Melodi Gama-3 seeds originated from Laboratory of Genetics, Faculty of Biology, Universitas Gadjah Mada, and commercial cultivars seeds, i.e., Action 434, Glamour Sakata, MAI, and LADIKA, respectively. The trial had been conducted at three variations of altitude i.e., mediumland, lowland, and beach shore, respectively, in period of rainy season. The quantitative traits, that were fruit weight and girth, flesh, and rind thickness, as well as vertical and horizontal diameter (longitudinal section), respectively, had been observed and measured at the Laboratory of Genetics, Faculty of Biology, Universitas Gadjah Mada. Data then analyzed with Honestly Significant Different test following balanced ANOVA, all using PKBT-STAT 2 software. Results showed that all the quantitative traits, except for flesh thickness, were influenced very significantly by interaction of cultivars x locations (P < 0.01). The Honestly Significant Difference test indicated that the Melodi Gama-3 had higher measurement of its quantitative traits (fruit weight: 2.68 kg; fruit girth: 55.45 cm; rind thicknesss: 0.93 – 1 cm; vertical diameter: 15.94 – 18.19 cm; horizontal diameter: 17.79 cm) than other cultivars. It was revealed that the Melodi Gama-3 was best planted at lowland altitude. Plant breeders should benefit from this study for the Melodi Gama-3 has great potency to be bred based on its traits comparison with commercial cultivars.